Ophiocordyceps anshunensis sp. nov., a new entomopathogenic fungus from O. nutans complex (Ophiocordycipitaceae, Ascomycota) - Guan, Yuhu; He, Chaoding; Ren, Yulin; Zhou, Ziqi; Zhang, Xu; Wang, Yao (Phytotaxa, 2025)
A new entomopathogenic fungus in the genus Ophiocordyceps from Southwestern China, is described and illustrated here under the name Ophiocordyceps anshunensis. It is characterized by 30-80 mm long stromata with smaller (2.4–5.0 × 1.2–2.8 mm) oval to ellipse shaped fertile head and 8.3−17.6 × 1.1–2.0 µm part-spores. According to phylogenetic analyses of combined ITS, LSU, TEF, RPB1, and RPB2 sequences, the new species is sister to O. nutans, from which differ by the aforementioned characteristics. A tabular comparison between the new species and related and similar taxa is provided.